2000
DOI: 10.1056/nejm200007273430402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lung-Volume–Reduction Surgery in Patients with Severe Emphysema

Abstract: In selected patients with severe emphysema, lung-volume-reduction surgery can improve FEV1, walking distance, and quality of life. Whether it reduces mortality is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
185
0
11

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(205 citation statements)
references
References 17 publications
9
185
0
11
Order By: Relevance
“…SZEKELY et al [191] reported that a 6-MWD ,200 m before or after pulmonary rehabilitation is an excellent preoperative predictor of unacceptable post-operative mortality at 6 months, with a specificity of 84%. Similarly, a randomised controlled study by GEDDES et al [192], to evaluate the effect of LVRS in patients with emphysema, indicated that a preoperative shuttle walk test (SWT) distance ,150 m was a predictor of high peri-operative mortality. Interestingly, in the National Emphysema Treatment Trial [193], exercise capacity was used to identify the subgroup of patients for whom LVRS has the most favourable survival and cost-effectiveness compared with medical therapy.…”
Section: Timed Walking Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…SZEKELY et al [191] reported that a 6-MWD ,200 m before or after pulmonary rehabilitation is an excellent preoperative predictor of unacceptable post-operative mortality at 6 months, with a specificity of 84%. Similarly, a randomised controlled study by GEDDES et al [192], to evaluate the effect of LVRS in patients with emphysema, indicated that a preoperative shuttle walk test (SWT) distance ,150 m was a predictor of high peri-operative mortality. Interestingly, in the National Emphysema Treatment Trial [193], exercise capacity was used to identify the subgroup of patients for whom LVRS has the most favourable survival and cost-effectiveness compared with medical therapy.…”
Section: Timed Walking Testsmentioning
confidence: 99%
“…KADIKAR et al [194] retrospectively observed the sensitivity and specificity of the 6-MWT to predict death in 145 patients who had undergone lung transplantation; a distance ,400 m appeared be an appropriate marker for listing patients for transplant. For LVRS, the threshold for a successful outcome has been reported to be ,150 m for the SWT [192] or 200 m for the 6-MWT [191].…”
Section: Timed Walking Testsmentioning
confidence: 99%
“…Lung volume reduction surgery (LVRS) has been shown to have a beneficial effect on lung function, submaximal exercise capacity and quality of life in selected patients with severe emphysema [1][2][3], although individual results classically demonstrate large scatter [1]. Initially, it was proposed that the increase in maximal expiratory flow (MEF) observed after LVRS was mainly due to an improvement in lung elastic recoil after the surgical procedure [4].…”
mentioning
confidence: 99%
“…Several large case series from centres with considerable experience have demonstrated a low operative mortality (v5%) and significant improvements in symptoms, pulmonary function, and exercise capacity in the short and intermediate term after LVRS [3][4][5][6][7]. Three prospective randomised studies confirmed functional improvements in the operated group, whereas this was not observed in the conservativelytreated control arm [8][9][10]. Nonetheless, controversy remained with respect to potential benefits and risk of the procedure [11,12].…”
mentioning
confidence: 96%
“…Initial enthusiasm for LVRS was soon dampened due to reports on surgical mortality rates of up to 17% [9]. A review of Medicare claims showed a 6-month mortality rate of 16.9% [15].…”
mentioning
confidence: 99%